Designing a roadmap towards a sustainable supply chain: A focus on the fashion industry. (20th August 2018) - Moretto, Antonella; Macchion, Laura; Lion, Andrea; Caniato, Federico; Danese, Pamela; Vinelli, Andrea
Abstract: Fashion companies are extremely sensitive to the new challenge emerging from recent sustainability scandals. Existing literature has debated sustainability extensively by considering practices of sustainability that companies should apply. However, little research has focused on the design of a proper sustainability roadmap from a supply chain (SC) perspective to address the steps involved in implementing sustainability practices. The objective of this study is to design a sustainability roadmap for fashion companies. Based on case studies of three tiers of three fashion SCs as an empirical basis, social and environmental sustainability practices were grouped into a five-step roadmap. The main result of the paper is a five-step roadmap, characterised in terms of practices and main goal. The roadmap is then discussed in terms of possible paths of developing, in terms of evolution within a step and among different steps.